The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1080/18811248.1996.9731971
|View full text |Cite
|
Sign up to set email alerts
|

The Passivation Effects of Magnesium Ion on PHWR Primary Heat Transfer System Structural Materials

Abstract: Zinc ion injection passivation technique is being used in BWRs in order to reduce the radiation field build-up around the reactor coolant system. In the case of PWRs and PHWRs, the chemistry of the primary coolant system and the materials of construction are different from those of BWRs. In the present paper, the results of studies on the effect of magnesium ion in modifying the oxide layers formed under PHWR chemistry conditions are reported. The experiments carried out at room temperature and at 265'C are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Fe ions in all three coupons were present in Fe 2? state and observed at 709.68 eV. A Cr2p 3/2 peak is expected at 574.4 eV if chromium is in Cr 0 state and at 577 eV if it is in Cr 3? state [10]. The peak position of chromium in the 577 eV state proves the presence of chromium in Cr 3? state in SUS304 and inconel(Incoloy-600).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Fe ions in all three coupons were present in Fe 2? state and observed at 709.68 eV. A Cr2p 3/2 peak is expected at 574.4 eV if chromium is in Cr 0 state and at 577 eV if it is in Cr 3? state [10]. The peak position of chromium in the 577 eV state proves the presence of chromium in Cr 3? state in SUS304 and inconel(Incoloy-600).…”
Section: Resultsmentioning
confidence: 85%
“…The peak position of chromium in the 577 eV state proves the presence of chromium in Cr 3? state in SUS304 and inconel(Incoloy-600). A Cr2p 1/2 peak was also observed at 587.1 eV binding energy [10] for both the SUS304 and Inconel cases. these figures, it shows clearly that Cr is not present in the top surface of carbon steel.…”
Section: Resultsmentioning
confidence: 85%
“…Hence, magnesium (Mg 2+ ) ion is being studied as an alternative for Zn 2+ ions. Reduction in corrosion product release from CS was observed due to Mg 2+ ion passivation in simulated PHWR-PHT coolant conditions [12]. Studies have shown that simultaneous presence of Zn 2+ and Ni 2+ ions in solution were effective in suppressing the cobalt deposition onto stainless steel surfaces in oxygenated high temperature water [13].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the type of reactor, either an oxidising formulation followed by a reducing formulation or only the latter is used for the purpose. [2][3][4] Permanganate based oxidising reagents such as alkaline permanganate, 5 nitric acid permanganate 5 and permanganic acid 6 are generally used for the pretreatment in the decontamination process to dissolve chromium from the iron, chromium and nickel containing oxide films formed on stainless steel and other chromium containing alloys. 7 During such process, the core material, which is zircaloy-2, will also come in contact with the decontamination solution.…”
Section: Introductionmentioning
confidence: 99%
“…Dilute chemical decontamination process is one of the methods adopted to remove the activity embedded in the oxide layers formed over these structural materials. Depending on the type of reactor, either an oxidising formulation followed by a reducing formulation or only the latter is used for the purpose 24. Permanganate based oxidising reagents such as alkaline permanganate,5 nitric acid permanganate5 and permanganic acid6 are generally used for the pretreatment in the decontamination process to dissolve chromium from the iron, chromium and nickel containing oxide films formed on stainless steel and other chromium containing alloys 7.…”
Section: Introductionmentioning
confidence: 99%